C-terminus Methionene Specifically Involved in Binding Corn Odorants to Odorant Binding Protein4 in Macrocentrus cingulum - Ahmed, Tofael; Zhang, Tiantao; Wang, Zhenying; He, Kanglai; Bai, Shuxiong (Frontiers in Physiology, 2017)
The soluble carrier proteins, odorant binding proteins (OBPs), transport odor molecules across the sensillar lymph to specific receptors within the antennal sensilla to trigger behavioral responses. Herein, McinOBP4 was characterized from the Macrocentrus cingulum, which is the specialist parasitic insect of Ostrinia furnacalis for better understanding of olfactory recognition mechanism of this wasp. The classical odorant binding protein McinOBP4 showed good binding affinity to corn green leaf volatiles. Real-time PCR experiments indicated that the McinOBP4 was primarily expressed in wasp antennae, with transcript levels differing by sex. Fluorescence assays indicate that, McinOBP4 binds corn green leaf volatiles including terpenoides and aliphatic alcohols as well as aldehydes with good affinity. We have also conducted series of binding assay with first mutant (M1), which lacked the last 8 residues and a second mutant (M2), with Met119 replaced by Leucine (Leu119). In the acidic conditions, affinity N-phenylnaphthylamine (1-NPN) to McinOBP4 and M1 were substantially decreased, but increase in basic condition with no significant differences. The lack of C-terminus showed reduced affinity to terpenoides and aliphatic alcohols as well as aldehydes compounds of corn odorants. The mutant M2 with Met119 showed significant reduction in binding affinity to tested odorants, it indicating that Met119 may be involved in binding these compounds through forming hydrogen bonds with the functional group of odorant compounds. These findings provide insight into the detailed chemosensory function of McinOBP4 in M. cingulum and help to develop low release agents that attract of this wasp to improve ecologically-friendly pest management strategy.